Kemandirian Keluarga Berencana (KB) pada Pasangan Usia Subur di Kota Yogyakarta - Susiana Sariyati; Sundari Mulyaningsih; Hamam Hadi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2014)
Family planning is part of the needs of the community, todays, by the government has given to the community. This condition was used by BKKBN as a trigger to improve toward independence. Yogyakarta Province (DIY) as the one province in Indonesia which has high number of active acceptors. In 2012, active acceptors has reached 34.373 (73.29%) of 47 339 couples of productive age (BKKBN 2012). This research aimed to know representation of KB independence in couples of childbearing age (EFA) in Yogyakarta 2013. This is a descriptive research with descriptive survey approach. The population of study was an active family planning participants with a sample size of 521. Sampling techniques was done by Probability Proportional to Size (PPS), while respondents were determined with random sampling technique. Data was analyzed using univariate analysis. In this study, contraception was widely obtained by couple of childbearing age with fully paying and health insurance total of 143 (52.2%) with the reason of having KB independence was because of economic factors at 128 respondents (46.7%). In conclusion, Independence KB in Yogyakarta can be represented that mostly KB is provided through paying full as the majority have a health insurance.